Detection of Parasites Contaminating Raw Consumable Vegetables in Kalar City, Kurdistan Region, Iraq - Hazhar M. Aziz (Academic Science Journal)
Intestinal parasitic infections are one of the most important health problems. Although fresh vegetables are considered as a vital element of a healthy diet, they are a potential source of human intestinal parasitic infections during production, collection, transportation, preparation and consumption. The present study was carried out to determine and detect the parasite contaminants of fresh vegetables that are sold at different open-aired markets in Kalar city, Kurdistan Region, Iraq. A total of 240 raw vegetable samples were examined by sedimentation technique after washing the samples with normal saline. Of the 240 samples, 124 (51.7%) were microscopically positive for intestinal parasites. Particularly, a high rate of contamination was recorded in cress (Lepidium sativum) with 70%. However, the least contaminated sample was lettuce (Lactuca sativa) with 36.7%. The most encountered parasite was Taenia spp. (egg 12.9%), whereas Trichuris trichiura (0.83%) was the least detected parasite. Since, the results emphasize the fresh vegetables are potential sources of transmission for intestinal parasites in central markets of Kalar city, strict hygienic measures should always be adopted to avoid parasitic contamination. Untreated sewage and the manure used by greengrocer as fertilizer can be implicated in vegetable contamination.